Phylogeny of marine Ainuyusurika tuberculata (Tokunaga) (Diptera: Chironomidae: Chironominae), with description of the immature stages - Han, Wu; Tang, Hongqu (Zootaxa, 2019)
The marine Chironomidae Ainuyusurika Sasa et Shirasaka, 1988, previously known from the adults only, is associated with its immature stages for the first time based on reared specimens from Oriental China. The larva resembles those of Sergentia Kieffer and Endochironomus Kieffer in the ventromental plate with an anteromedial projection and the 5-segmented antenna with opposite Lauterborn organs. The pupal thoracic horn has 12 branches at maximum and netted tergite spinulation which appears to be similar to those of Polypedilum Kieffer, Endotribelos Grodhaus, Phaenopsectra Kieffer and Sergentia. The phylogenetic relationship was furtherly explored through molecular analysis based on concatenation of five gene makers (18S, 28S, CAD1, CAD4 and COI-3P) using both mixed-model Bayesian and maximum likelihood inference methods. The result shows Ainuyusurika is nested with an assemblage of Endochironomus, Phaenopsectra and Endotribelos. We concluded that Ainuyusurika is a good independent genus showing affinity with Endochironomus-Phaenopsectra related genera.